ANALYSIS OF PRIMARY SCHOOL STUDENTS' MATHEMATICAL CONCEPTUAL UNDERSTANDING BASED ON LEARNING INTEREST - Elinda, Elinda; Aminah, Neneng; Pramuditya, Surya Amami; Maharani, Anggita (KALAMATIKA Jurnal Pendidikan Matematika, 2023)
This research utilized a qualitative approach to providing a descriptive and in-depth exploration of elementary school students' mathematical and conceptual understanding of their learning interests. The study includes 20 participants, selected based on the categories of their learning interests, with three representatives chosen from each category. Participants are also selected based on their age, according to Piaget's theory, and communication abilities. Data collection techniques involve data reduction, data categorization, and data verification. Based on the research findings and discussions, it can be concluded that students with high learning interests demonstrate a strong understanding of mathematical concepts. Similarly, students with moderate learning interest exhibit a commendable grasp of mathematical concepts, while students with low learning interest tend to have lower conceptual understanding. For future research, it is recommended to explore the use of instructional media to assess children's learning interests.